2020
DOI: 10.1101/2020.01.25.20018820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incorporating Nonlinear Kinetics to Improve the Predictive Performance of Population Pharmacokinetic Models for Ciclosporin in Adult Renal Transplant Recipients: A Comparison of Modelling Strategies

Abstract: Aim: Ciclosporin (CsA) has been shown to follow nonlinear pharmacokinetics in renal transplant recipients who received Neoral-based triple immunosuppressive therapy. Some of these nonlinear properties have not been fully considered in population pharmacokinetic (popPK) analysis. Therefore, the aim of this study was to determine the potential influence of nonlinearity and the functional forms of covariates on model predictability. Methods: A total of 2969 CsA whole-blood measurements, including 1328 pre-dose an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…CsA DD was identified as a significant covariate for CL, which declined with the decrease of CsA DD. This tendency was also observed in the previous studies, which indicated nonlinear clearance of the drug 31,32 . Such nonlinear kinetics phenomenon may be partially due to the saturated distribution into red blood cells or the inhibitory effects of CsA on CYP3A4/P‐glycoprotein 31 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…CsA DD was identified as a significant covariate for CL, which declined with the decrease of CsA DD. This tendency was also observed in the previous studies, which indicated nonlinear clearance of the drug 31,32 . Such nonlinear kinetics phenomenon may be partially due to the saturated distribution into red blood cells or the inhibitory effects of CsA on CYP3A4/P‐glycoprotein 31 .…”
Section: Discussionsupporting
confidence: 81%
“…This tendency was also observed in the previous studies, which indicated nonlinear clearance of the drug. 31,32 Such nonlinear kinetics phenomenon may be partially due to the saturated distribution into red blood cells or the inhibitory effects of CsA on CYP3A4/P-glycoprotein. 31 Further studies with intensive sampling are needed to explore the nonlinear kinetics phenomenon of CsA.…”
Section: Discussionmentioning
confidence: 99%
“…CsA exposure in the early phases after transplantation was 15.4% lower than that in the stable period when the same CsA dose was administered. The increased CsA bioavailability in the initial period may correlate with improved absorption in the intestine [42] and co-administration with steroids [43], which can activate the pregnane X receptor (PXR) to upregulate CYP3A and P-gp activity [35,44]. Therefore, CsA dosage should be reduced when steroids are co-administered [20].…”
Section: Discussionmentioning
confidence: 99%